2008
DOI: 10.1002/bit.22213
|View full text |Cite
|
Sign up to set email alerts
|

Impact of varying electron donors on the molecular microbial ecology and biokinetics of methylotrophic denitrifying bacteria

Abstract: The goal of this study was to identify bacterial populations that assimilated methanol in a denitrifying sequencing batch reactor (SBR), using stable isotope probing (SIP) of (13)C labeled DNA and quantitatively track changes in these populations upon changing the electron donor from methanol to ethanol in the SBR feed. Based on SIP derived (13)C 16S rRNA gene clone libraries, dominant SBR methylotrophic bacteria were related to Methyloversatilis spp. and Hyphomicrobium spp. These methylotrophic populations we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
76
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(80 citation statements)
references
References 73 publications
4
76
0
Order By: Relevance
“…Compared with methanol-fed R1, the lower sulfate generation and residual TOC concentration were observed in the ethanol-fed R2. This can be explained by the fact that denitrifying bacteria are more accessible to ethanol than methanol (Baytshtok et al, 2009). Some researchers also reported that ethanol fostered higher specific denitrification rates than methanol (Martin et al, 2009;Mokhayeri et al, 2008;Lu and Chandran, 2010;Salminen et al, 2014).…”
Section: Performance Of Mixotrophic Anfb-mbrsmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared with methanol-fed R1, the lower sulfate generation and residual TOC concentration were observed in the ethanol-fed R2. This can be explained by the fact that denitrifying bacteria are more accessible to ethanol than methanol (Baytshtok et al, 2009). Some researchers also reported that ethanol fostered higher specific denitrification rates than methanol (Martin et al, 2009;Mokhayeri et al, 2008;Lu and Chandran, 2010;Salminen et al, 2014).…”
Section: Performance Of Mixotrophic Anfb-mbrsmentioning
confidence: 99%
“…Nitrite and nitrous oxide concentrations for the ethanol-fed mixotrophic denitrification peaked before the methanol-fed process, and relatively lower nitrite and nitrous oxide accumulations were observed in the ethanol-fed process, indicating ethanol-fed mixotrophic denitrification had higher denitrification biokinetics than methanol. In fact, many commercially available carbon sources induce higher denitrification activity than methanol (Baytshtok et al, 2009;Bodík et al, 2009;Lu et al, 2014;Nyberg et al, 2004). Nitrogen balances were determined to further elucidate the removal mechanisms of sulfur-based denitrification.…”
Section: N-labeling Denitrification Processmentioning
confidence: 99%
See 1 more Smart Citation
“…Some strains have been characterized by their denitrification capacities (2)(3)(4)(5). They have often been identified as major players in denitrification systems supplemented with methanol (4,(6)(7)(8), and their presence has been associated with high denitrification rates (9,10).…”
mentioning
confidence: 99%
“…M ethanol-enhanced denitrification as part of sewage treatment is a well-described phenomenon (1), and a number of methylotrophs have been implicated in this process, carried out by mixed cultures (2)(3)(4)(5). However, the role of denitrification and its connection to methylotrophy in natural systems is not well understood, and data from studies involving pure cultures of methylotrophs are sparse.…”
mentioning
confidence: 99%